Optimization Of Raw Material Inventory for Rayon Yarn at CV XYZ Using the EOQ-Lagrange Multiplier Method and Theory Of Constraint - Virga, Avril; Donoriyanto, Dwi Sukma (The Indonesian Journal of Computer Science, 2025)
CV XYZ is a manufacturer of woven sarong in East Java. The problem faced challenges with excess rayon yarn inventory, leading to overcapacity in storage and high costs. Additionally, suppliers' minimum order requirements exacerbate the issue. This study uses the Lagrange Multiplier and Theory of Constraint methods to optimize rayon yarn inventory to minimize costs and storage needs. The results reveal an adjusted storage space requirement of 84 m³, with details of the total storage space and the minimum order quantity, namely rayon yarn R80/2 of 28.32 m³ (147 boxes), R60/2 of 25.80 m³ (134 boxes), and R32/2 of 29.88 m³ (155 boxes). This method also reduces the total inventory cost to IDR 30,640,592, achieving a remarkable 84.61% saving (IDR 168,574,408) compared to the company's current process. The findings demonstrate that combining Lagrange Multiplier and TOC effectively addresses storage limitations, optimizes order quantities, and minimizes inventory costs.